The audience of Ammianus Marcellinus and the Circulation of Books in the Late Roman World - Sánchez, Darío Néstor (2018)
Since the late nineteenth century, studies of Ammianus' audience have reached widely divergent conclusions. Research has focused on two opposed theses: while some scholars have seen the pagan senatorial aristocracy as the audience of the Res Gestae, others have assigned that role to the imperial bureaucracy. However, in thinking that a work could reach -or target- exclusively the members of a specific social group, the prevalent views on Ammianus' audience contradict what we know about the circulation of books in the late Roman world. In contrast to previous research, this study proposes a new approach based on an analysis of the information available on book circulation in Ammianus' time. This analysis shows that the audience of the Res Gestae was most likely socially diverse.